Quantitative calculation method of the collision risk for collision avoidance in ship navigation using the CPA and ship domain. Issue 3 (13th May 2021) - Ha, Jisang; Roh, Myung-Il; Lee, Hye-Won
Abstract: Collision risk (CR) assessment is necessary for avoiding collisions with other ships. The CR can be used to make decisions on collision avoidance. In this respect, the ship domain and the closest point of approach (CPA)-based methods have been proposed to assess the CRs. However, the ship domain method is limited in terms of the quantitative calculation of the CR, whereas the CPA-based method does not guarantee reliable collision avoidance. In this study, an improved method is proposed for the quantitative calculation of the CR in ship navigation that combines the advantages of two existing methods. The proposed method calculates the CR using the CPA and defines the ship domain as a critical value of the CR to ensure reliable collision avoidance. In this process, the CR value of another ship on the boundary of the ship domain is calculated as 1, which implies that collision occurs, and the coefficients for the CR calculation are adjusted considering the distance from the ship domain. Furthermore, the manoeuvring performance and the heading angle of the ships are considered in the calculation of the CR. To evaluate the proposed method, it is applied to various examples, including a comparison with previous methods. The results show that the proposed method can be used to obtain a quantitative CR for collision avoidance. Graphical Abstract: